Recent advances in cell membrane-coated porphyrin-based nanoscale MOFs for enhanced photodynamic therapy - Zou, Yutao; Wu, Junjie; Zhang, Qiuyun; Chen, Jiayi; Luo, Xuanxuan; Qu, Yijie; Xia, Rui; Wang, Weiqi; Zheng, Xiaohua (Frontiers in Pharmacology, 2024)
Porphyrins-based nanoscale metal-organic frameworks (nMOFs) has been widely utilized to kills tumor cells by generating cytotoxic reactive oxygen species (ROS).However, porphyrin based nMOFs (por-nMOFs) still face challenges such as rapid immune clearance and weak tumor targeting. Researchers have discovered that using a top-down biomimetic strategy, where nMOFs are coated with cell membranes, can promote long blood circulation, evade the reticuloendothelial system, and improve cancer cell targeting, thereby significantly enhancing the photodynamic therapy (PDT) effect of nMOFs. This review summarizes the recent work on different cell membranes-coated por-nMOFs for enhanced tumor PDT. This review details the changes in physicochemical properties, enhanced homotypic cancer cell-selective endocytosis, improved tumor tissue targeting, and increased cytotoxicity and effective in vivo tumor suppression after the nMOFs are wrapped with cell membranes.Additionally, this review compares the biological functions of various types of cell membranes, including cancer cell membranes, red blood cell membranes, aptamer-modified red blood cell membranes, and hybrid membranes from the fusion of cancer and immune cells. The review highlights the enhanced immunogenic cell death function when using hybrid membranes derived from the fusion of cancer and immune cell membranes. By summarizing the augmented PDT effects and the combined antitumor outcomes with other therapeutic modalities, this review aims to provide new insights into the biomedical applications of por-nMOFs and offer more references for the preclinical application of porphyrin-based photosensitizers.